Guided bone regeneration membrane as well as preparation method and application thereof

Through the double-layer GBR film-covalent self-assembled collagen zinc film, combined with covalent surface modification and self-assembly technology, the problems of insufficient biocompatibility, degradation rate and osteoinductivity of existing membranes are solved, and zinc ions are realized The sustained release and bone regeneration effects avoid secondary surgery and improve the mechanical properties and biocompatibility of the membrane.

CN119185664AActive Publication Date: 2024-12-27PEKING UNIV SCHOOL OF STOMATOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411552187.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2024-12-27
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing guided bone regeneration membranes have shortcomings in biocompatibility, degradation rate and osteoinduction, especially the difficulty in releasing zinc ions to promote bone regeneration, and require secondary surgery to remove, which increases the risk of infection.

Method used

Using double-layer GBR film-covalent self-assembled collagen zinc film (ss-HMC/Zn), through covalent surface modification and self-assembly technology, zinc is combined with layered functional mineralized collagen to form good biocompatibility, Degradable and osteoinductive membranes achieve uniform sustained release of zinc ions.

Benefits of technology

It improves the mechanical strength and support performance of the membrane, controllable degradation rate, avoids secondary surgery, enhances the bone regeneration effect, and promotes in situ bone regeneration without the need for external growth factors or cells in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119185664A_ABST
    Figure CN119185664A_ABST
Patent Text Reader

Abstract

The invention provides a guided bone regeneration membrane as well as a preparation method and application thereof. The guided bone regeneration membrane comprises a substrate layer comprising at least 99% by weight of zinc; and at least one self-assembled mineralized collagen layer, the self-assembled mineralized collagen layer is arranged on the base material layer, and the self-assembled mineralized collagen layer comprises collagenous fibers and apatite crystals bonded with the collagenous fibers. The guided bone regeneration membrane disclosed by the invention not only has a barrier function, but also has good biocompatibility, degradability and osteoinductivity, and can uniformly and slowly release zinc, so that the problem that the treatment application effect of the existing guided bone regeneration membrane is limited due to a single material structure is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of medical materials, and in particular to a guided bone regeneration membrane, a preparation method thereof and an application thereof. Background Art

[0002] Guided Bone Regeneration Membrane (GBR) technology is a treatment method that uses a barrier membrane to achieve bone tissue regeneration. Among them, the GBR membrane, as the key to GBR technology, can seal the bone defect area, prevent non-osteoblasts from growing in, and create a good environment for bone tissue regeneration. The ideal GBR membrane should have good biocompatibility, a suitable degradation rate, and sufficient support to seal the defect.

[0003] Currently, GBR membranes on the market can be divided into absorbable membranes and non-absorbable membranes. Among them, the mainstream absorbable collagen membranes have insufficient mechanical properties and uncontrollable degradation rates; while non-absorbable membranes require secondary surgery to remove, which can easily cause wound exposure and infection. In addition, existing GBR membrane materials often lack bone inductivity and require bone filling materials, and cannot have both degradability and mechanical support properties.

[0004] The optimization and modification of existing GBR membranes focus on: component optimization such as loading bioactive factors and stem cells, structural optimization such as surface modification, etc. Degradable metal zinc has attracted extensive attention due to its good degradation performance and biocompatibility. However, since the release of excessive zinc ions can cause cytotoxicity and inhibit osteogenesis, finding a suitable method to slowly release zinc ions and promote osteogenesis is very important for guiding bone regeneration.

[0005] However, the prior art still lacks a biocompatible GBR membrane that can both slowly release zinc ions and guide bone regeneration. Summary of the invention

[0006] In view of the shortcomings of the existing GBR membrane, the problem to be solved by the present invention is to prepare a new double-layer GBR membrane - covalent self-assembled collagen zinc membrane, which combines zinc and hierarchical functional mineralized collagen (Hierarchical Mineralized Collagen / Zn via Surface Covalent Modification and Self-Assembly, ss-HMC / Zn) through covalent surface modification and self-assembly, so that it not only plays a barrier function, but also has good biocompatibility, degradability, bone induction, and uniform sustained release of zinc, thereby solving the problem that the existing GBR membrane has a single material structure that limits its therapeutic application effect.

[0007] In order to solve the above technical problems, this application adopts the following technical solutions:

[0008] 1. A guided bone regeneration membrane, comprising: a substrate layer, the substrate layer comprising at least 99 weight % zinc; and at least one self-assembled mineralized collagen layer, the self-assembled mineralized collagen layer being disposed on the substrate layer and comprising collagen fibers and apatite crystals bonded to the collagen fibers.

[0009] Optionally, the mineralized collagen layer is formed by first forming a porous collagen scaffold layer on a substrate layer, and then catalyzing a mineralizing liquid in the pores of the collagen scaffold layer using polyacrylic acid as a catalyst, wherein the composition of the mineralizing liquid is:

[0010]

[0011] Optionally, the concentration of polyacrylic acid is 0.20-0.30 mM relative to the total amount of the mineralization solution.

[0012] Optionally, the substrate layer is a zinc film that has been surface pretreated, wherein the surface pretreatment is selected from any one of an acid etching pretreatment in a phosphoric acid solution with a pH value of 2-3 and a mechanical grinding pretreatment using sandpaper of various grits.

[0013] Optionally, the thickness of the mineralized collagen layer accounts for 74-80% of the total thickness of the guided bone regeneration membrane, wherein in the mineralized collagen, the content of the collagen fibers is 80 wt %-85 wt %, and the content of the apatite crystals is 15 wt %-20 wt %.

[0014] Optionally, the guided bone regeneration membrane has a yield strength of 45-80 MPa, an ultimate tensile strength of 55-80 MPa, and a water contact angle of 30-53°.

[0015] 2. A method for preparing a guided bone regeneration membrane, comprising the following steps:

[0016] S1-providing a substrate layer, the substrate layer comprising at least 99% by weight zinc;

[0017] S2-applying a collagen solution on the substrate layer to allow the collagen to self-assemble into a collagen fiber layer, and drying and shaping to form a porous scaffold layer; and

[0018] S3- Adding mineralizing liquid into the pores of the porous scaffold layer to perform mineralization treatment, and catalyzing the mineralizing liquid in the pores of the collagen scaffold layer to form apatite crystals, thereby obtaining the guided bone regeneration membrane.

[0019] Optionally, the substrate layer is subjected to surface pretreatment before step S2, and then the collagen solution is applied to the pretreated substrate layer, wherein the surface pretreatment comprises at least one of the following:

[0020] C) pre-treatment of the substrate layer by acid etching in a mixed solution of zinc nitrate and phosphoric acid at a pH of 2-3, or

[0021] D) The substrate layer is mechanically ground with silicon carbide sandpaper of 600, 800, 1200, 1500 and 2000 meshes in sequence.

[0022] Optionally, step S2 comprises dripping a type I procollagen solution having a concentration of 0.5-2.0 mg / ml onto the substrate layer at a rate of 0.5 to 2 ml / min, self-assembling for 24-48 hours, and then freeze-drying for 12-24 hours to dry and shape.

[0023] Optionally, the method further comprises, after the surface pretreatment, ultrasonically cleaning the surface-treated substrate with distilled water, acetone and anhydrous ethanol at a temperature of 40-60° C. for 1-2 minutes, respectively.

[0024] Optionally, step S3 includes adding 1-3 ml of the mineralization solution into each of the pores, replacing the mineralization solution every 2-3 days, and continuously mineralizing at 25-37° C. for 5-10 days.

[0025] 3. Use of a guided bone regeneration membrane in the preparation of a medical device for promoting in situ bone regeneration in vivo.

[0026] Optionally, the promoting in situ bone regeneration in vivo is selected from at least one of promoting in situ bone regeneration in vivo by promoting cell recruitment, promoting in situ bone regeneration in vivo by promoting M2 macrophage polarization, promoting in situ bone regeneration in vivo by enhancing vascularization, and promoting in situ bone regeneration in vivo by activating BMP2-related pathways.

[0027] Compared with the GBR membrane currently used in clinical practice, the ss-HMC / Zn membrane of the present invention has the following advantages:

[0028] Compared with the existing GBR collagen membrane, it has high mechanical strength, strong supporting performance and controllable degradation rate; compared with the existing GBR artificial synthetic polymer membranes such as polytetrafluoroethylene and metal titanium membranes, it has strong biocompatibility, can be degraded in the body, does not require secondary removal, and can guide and promote in situ bone regeneration without adding exogenous growth factors and cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A: a process flow chart of a method for preparing a GBR membrane according to one embodiment of the present invention; B: a schematic diagram of a process for preparing a GBR membrane according to one embodiment of the present invention.

[0031] Figure 2A: The morphology of the Zn surface (lower part) of the GBR membrane prepared in Example 1 (covalent surface modification) and Example 2 (surface micro-polishing) of the present invention (from left to right, schematic diagram, SEM photo of the sample of Example 1 and SEM photo of the sample of Example 2); B: The morphology of the material interface of the GBR membrane prepared in Example 1 (covalent surface modification) and Example 2 (surface micro-polishing) of the present invention (from left to right, schematic diagram, SEM photo of the sample of Example 1 and SEM photo of the sample of Example 2); C: The morphology of the material interface of the GBR membrane prepared in Example 1 (covalent surface modification) and Comparative Example 2 The morphology of the collagen surface of the material of the GBR membrane (from left to right are a schematic diagram, the SEM photograph of the sample of Example 1 and the SEM photograph of the sample of Comparative Example 1); D: FTIR graph of the upper surface of the GBR membrane prepared by Comparative Example 1 (upper curve) and Example 1 (lower curve); E: Yield strength graph of the samples of Comparative Example 1, Comparative Example 2 and Example 1 measured by AFM; F: Ultimate tensile strength values ​​of the samples of Comparative Example 1, Comparative Example 2 and Example 1 measured by AFM and G: Contact angles of the surfaces of the samples of Comparative Example 1, Comparative Example 2 and Example 1 measured using a contact angle meter.

[0032] Figure 3 A: scanning electron microscope image of the GBR film prepared in Example 1 and the measured energy dispersive spectra (EDS); B: transmission electron microscope (TEM) images of the GBR film samples of Example 1 and Comparative Example 1 are shown respectively.

[0033] Figure 4 The Zn content in the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) is shown. 2+ Graph showing the release of ions over time in saline.

[0034] Figure 5A: Immunofluorescence photos of live-death detection of human bone marrow stem cells inoculated into samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) one day after inoculation; B: Immunofluorescence photos of human bone marrow stem cells inoculated into samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) one day after inoculation; C: SEM photos of human bone marrow stem cells inoculated into samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn); D : The cell activity of human bone marrow stem cells inoculated into the blank control, comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) samples within 5 days by CCK-8 experiment; E: Immunofluorescence staining photos of the samples of comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) after 7 days of osteogenic induction culture; F: ALP staining of the samples of comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) after 7 days of osteogenic induction culture Photos; G: Expression of RUNX2 and ALP after 7 days of osteogenic induction culture of samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn); H: Immunofluorescence staining photos of samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture; I: ARS staining photos of samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture Tablets; J: expression of BMP2 and OCN of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture; K: ALP values ​​of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 7 days of osteogenic induction culture; and L: optical density values ​​(OD values) of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture.

[0035] Figure 6A: The samples of blank control, comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) were implanted into rat skull defects, and after 6 weeks of observation, the in vivo osteogenesis was observed using Micro-CT, H&E, and Masson staining; B: The samples of blank control, comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) were implanted into rat skull defects, and after 12 weeks of observation, the in vivo osteogenesis was observed using Micro-CT, H&E, and Masson staining; C: The samples of blank control, comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) were implanted into rat skull defects, and the bone density (BMD) and bone volume (BV) were detected by Micro-CT after 6 and 12 weeks of implantation.

[0036] Figure 7 It was shown that the GBR membrane of the present invention activated multiple pathways related to osteogenesis, angiogenesis, and cell recruitment. DETAILED DESCRIPTION

[0037] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0038] In this article, collagen self-assembly refers to the orderly arrangement of collagen to form a collagen fiber structure through non-covalent interactions between collagen molecules under static equilibrium conditions.

[0039] In this article, collagen fiber mineralization refers to the deposition of nano-hydroxyapatite crystals inside the collagen fibers and their orderly arrangement to form mineralized collagen fibers.

[0040] In this article, Portland cement was purchased from Lehigh Cement Company. The official website is: https: / / www.lehighwhitecement.com / en / library / product-data-sheets.

[0041] Guided bone regeneration (GBR) membrane is currently a widely used clinical method and treatment key in the treatment of bone defect regeneration. However, the existing GBR barrier membrane biomaterials cannot fully meet the basic material characteristics of the ideal barrier membrane. Non-absorbable membranes are often exposed to secondary infections during clinical applications, thus affecting bone integration. The acidic products released during the degradation of aliphatic polymers may cause a strong inflammatory response, leading to the absorption of regenerated bone. Compared with synthetic polymers, collagen has better biocompatibility and biodegradability, but the degradation rate is difficult to control, the mechanical properties are poor, and the strength to maintain effective space is insufficient, which limits the application of collagen barrier membranes.

[0042] The present invention provides a combination of a pure zinc membrane (zinc content 99.00 wt % or higher, preferably 99.99 wt % or higher) and a functional hierarchical mineralized collagen membrane (HMC), thereby providing an improved GBR membrane that has excellent mechanical properties and / or degradation rate and can guide and promote in situ bone regeneration without adding exogenous growth factors and cells.

[0043] HMC has the hierarchy and nanostructure of natural bone, which provides a good microenvironment for cell recruitment and osteogenic differentiation. Its degradation rate is consistent with the rate of bone ingrowth. It has been used as a bone filling material and has achieved good results. Its porous structure makes it possible to release zinc slowly.

[0044] Therefore, in one aspect, the present invention provides a guided bone regeneration membrane, comprising: a substrate layer, the substrate layer comprising at least 99% by weight of zinc; and at least one self-assembled mineralized collagen layer. The self-assembled mineralized collagen layer can be disposed on the substrate layer and comprises collagen fibers and apatite crystals bonded to the collagen fibers. Apatite can include hydroxyapatite, chloroapatite, etc.

[0045] Preferably, the substrate layer may be a pure zinc film or zinc foil, for example, a pure zinc film with a purity of 99.990 to 99.998% and a thickness of 20-30 μm (preferably 30 μm).

[0046] Preferably, the mineralized collagen layer is formed by first forming a porous collagen scaffold layer on the substrate layer, and then catalyzing the mineralization liquid in the pores of the collagen scaffold layer with polyacrylic acid as a catalyst. The composition of the mineralization liquid may be:

[0047]

[0048] like Figure 1 As shown in A, the substrate layer can be a zinc film that has been surface pretreated. The surface pretreatment can be selected from any one or both of acid etching pretreatment in a phosphoric acid solution with a pH value of 2-3 (pretreatment method 1) and mechanical grinding pretreatment using sandpaper of various grain sizes (pretreatment method 2).

[0049] Specifically, the first pretreatment method may include surface covalent modification. The zinc film is pretreated with acid etching for 60 seconds using a mixed solution of Zn(NO3)2 (0.07M) and H3PO4 (0.15M) (pH adjusted to 2.5-3).

[0050] The second pretreatment method may include micro-grinding, for example, the zinc film is mechanically ground with 600, 800, 1200, 1500 and 2000 grit silicon carbide sandpaper for 3 minutes in sequence.

[0051] like Figure 1 As shown in B, the guided bone regeneration membrane may include at least one self-assembled mineralized collagen layer, preferably including 3-10 self-assembled mineralized collagen layers from bottom to top. The mineralized collagen layer may include collagen fibers, as well as Ca and P. The mineralized collagen layer may include apatite. The collagen fibers are bonded together by apatite. Mineralization is carried out by catalyzing the mineralization liquid in the pores of the collagen scaffold layer with polyacrylic acid as a catalyst. Therefore, the mineralization liquid may include NaCl, KCl, Na2HPO4, K2HPO4·3H2O, Na3N, silicate cement and polyacrylic acid.

[0052] The content of the collagen fibers is 80-85% by weight relative to the total weight of the guided bone regeneration membrane, and the content of the apatite crystals is 15-20% by weight relative to the total weight of the guided bone regeneration membrane. The thickness of the mineralized collagen layer accounts for 74-80% relative to the total thickness of the guided bone regeneration membrane.

[0053] Preferably, the guided bone regeneration membrane has a yield strength of 45-80 MPa, an ultimate tensile strength of 55-80 MPa, and a water contact angle of 30-53°.

[0054] In a second aspect, the present invention provides a method for preparing a guided bone regeneration membrane, comprising the following steps:

[0055] S1-providing a substrate layer, the substrate layer comprising at least 99% by weight zinc;

[0056] S2-applying a collagen solution on the substrate layer to allow the collagen to self-assemble into a collagen fiber layer, and drying and shaping to form a porous scaffold layer; and

[0057] S3- Adding mineralizing liquid into the pores of the porous scaffold layer to perform mineralization treatment, and catalyzing the mineralizing liquid in the pores of the collagen scaffold layer to form apatite crystals, thereby obtaining the guided bone regeneration membrane.

[0058] Preferably, the substrate layer is subjected to surface pretreatment before step S2, and then the collagen solution is applied to the pretreated substrate layer, wherein the surface pretreatment comprises at least one of the following:

[0059] A) Pre-treatment of the substrate layer by acid etching in a mixed solution of zinc nitrate and phosphoric acid at a pH of 2-3, or

[0060] B) The substrate layer is mechanically ground with silicon carbide sandpaper of 600, 800, 1200, 1500 and 2000 grits in sequence.

[0061] Preferably, step S2 comprises dripping a type I procollagen solution having a concentration of 0.5-2.0 mg / ml onto the substrate layer at a rate of 0.5-2 ml / min, self-assembling for 24-48 hours, and then freeze-drying for 12-24 hours to dry and shape.

[0062] Preferably, the method for preparing the guided bone regeneration membrane further comprises, after the surface pretreatment, ultrasonically cleaning the surface-treated substrate with distilled water, acetone and anhydrous ethanol at a temperature of 40-60° C. for 1-2 minutes respectively.

[0063] Optionally, step S3 includes adding 1-3 ml of the mineralization solution into each of the pores, replacing the mineralization solution every 2-3 days, and continuously mineralizing at 25-37° C. for 5-10 days.

[0064] In a specific embodiment, Figure 1 As shown in A, the preparation method of guided bone regeneration membrane comprises the following steps:

[0065] - Surface pretreatment of pure zinc film, which may include pretreatment method one or pretreatment method two, treatment method one includes immersing the pure Zn film (purity 99.998%) in a mixed solution composed of zinc nitrate (Zn(NO3)2, 0.07M) and phosphoric acid (H3PO4, 0.15M)), adjusting the pH to 2.5, and immersing for 60s; pretreatment method two may include mechanically grinding the pure Zn film (purity 99.998%) with 600, 800, 1200, 1500 and 2000 grit silicon carbide sandpaper for 3 minutes.

[0066] - The surface pretreated Zn film was ultrasonically cleaned at 55°C and 36kHz for 1-2 minutes in the order of distilled water, acetone and anhydrous ethanol.

[0067] - The treated samples were vacuum dried.

[0068] - A 1 mg / mL type I procollagen solution was dropped onto the Zn film surface at a rate of 1 mL / min and self-assembled for 24-48 hours to form collagen fibrils (ss-HC / Zn).

[0069] - The assembled ss-HC / Zn was placed in a 24-well plate, frozen in a -20°C refrigerator for 24 hours to form, and freeze-dried for about 12 hours to obtain a sponge-like three-dimensional porous collagen scaffold material.

[0070] - The three-dimensional porous collagen scaffold material was mineralized in a twenty-four-well plate for 7 days, the temperature was maintained at 37°C, 1 mL of mineralization solution (Table 1) was added to each well, and the mineralization solution was replaced every 2-3 days.

[0071] -After continuous mineralization for 7-10 days, a double-layer GBR membrane ss-HMC / Zn was obtained.

[0072] like Figure 1 As shown in B, in another embodiment, the preparation method of guided bone regeneration membrane includes: providing Zn foil, performing surface covalent modification or micro-polishing on the Zn foil to obtain pretreated Zn foil; dropping the original collagen solution onto the pretreated Zn foil, and gradually performing self-assembly from bottom to top to obtain an ordered array layer of collagen fibers, applying a mineralizing solution containing P and Ca to the ordered array layer of collagen fibers for mineralization, and continuously mineralizing for 7 days to obtain ss-HMC / Zn.

[0073] In a third aspect, the present invention provides use of a guided bone regeneration membrane in preparing a medical device for promoting in situ bone regeneration in vivo.

[0074] Preferably, promoting in situ bone regeneration in vivo is selected from at least one of promoting in situ bone regeneration in vivo by promoting cell recruitment, promoting in situ bone regeneration in vivo by promoting M2 macrophage polarization, promoting in situ bone regeneration in vivo by enhancing vascularization, and promoting in situ bone regeneration in vivo by activating BMP2-related pathways.

[0075] example

[0076] The invention is further described in conjunction with the following specific examples. It should be understood that the specific examples described herein are only used to explain the invention and are not used to limit the invention.

[0077] This example includes the following aspects:

[0078] 1) Preparation and characterization of a novel double-layer GBR membrane ss-HMC / Zn;

[0079] 2) In vitro and in vivo experiments were used to detect the sustained release effect of ss-HMC / Zn on zinc ions;

[0080] 3) In vitro experiments to detect the biocompatibility of ss-HMC / Zn;

[0081] 4) In vitro and in vivo experiments were used to detect the regulatory effect of ss-HMC / Zn on the osteogenic differentiation of human bone marrow mesenchymal stem cells;

[0082] 5) In vivo experiments were used to detect the intrinsic mechanism of ss-HMC / Zn promoting skull defect in rats.

[0083] Embodiment 1:

[0084] Zinc film pretreatment

[0085] The pure Zn film (purity 99.998%, thickness 30μm) sample was immersed in a mixed solution of zinc nitrate (ZnNO3[aq], 0.07M) and phosphoric acid (H3PO4[aq], 0.15M), the pH was adjusted to 2.5, and the sample was immersed for 60s. The zinc film after acid etching was ultrasonically cleaned at 55℃ and 36kHz in the order of distilled water, acetone and anhydrous ethanol for 1-2 minutes. The treated sample was vacuum dried.

[0086] Functional mineralized collagen (HMC) assembly: After zinc film pretreatment, functional mineralized collagen (HMC) was self-assembled on the zinc film surface by a "bottom-up" method. Specifically, a type I procollagen solution (Corning, NY, USA, 3500 Da) with a procollagen molecule concentration of 1 mg / mL was dripped onto the Zn surface at a rate of 1 mL / min and self-assembled for 24 hours to form collagen fibrils (ss-HC / Zn); then, the assembled ss-HC / Zn was placed in a 24-well plate, frozen in a refrigerator at -20°C for 24 hours to form, and freeze-dried for about 12 hours to obtain a sponge-like three-dimensional porous collagen scaffold material. The three-dimensional porous collagen scaffold material was mineralized in a twenty-four-well plate for 7 days, and the temperature was maintained at 37°C. 1 mL of mineralization solution was added to each well of the three-dimensional porous collagen scaffold material, in which 0.25 mM polyacrylic acid (Table 1) was added, and the mineralization solution was replaced every 2-3 days. Thus, ss-HMC / Zn of Example 1 was obtained. Figure 1 As shown in A and B.

[0087] Table 1

[0088]

[0089]

[0090] Example 2

[0091] Zinc film pretreatment

[0092] Pure Zn film (purity 99.998%, thickness 30 μm) samples were mechanically ground with 600, 800, 1200, 1500 and 2000 grit silicon carbide sandpaper. Then, the material was ultrasonically cleaned at 55°C and 36kHz for 1-2 minutes using de-distilled water, ethanol and acetone in sequence. The cleaned samples were dried in vacuum.

[0093] Functional mineralized collagen (HMC) assembly: After zinc film pretreatment, functional mineralized collagen (HMC) was self-assembled on the zinc film surface by a "bottom-up" method. First, a type I procollagen solution (Corning, NY, USA, 3500Da) with a procollagen molecule concentration of 1 mg / mL was dripped onto the Zn surface at a rate of 1 mL / min, and self-assembled for 24 hours to form collagen fibrils (ss-HC / Zn); then the assembled ss-HC / Zn was placed in a 24-well plate, frozen in a refrigerator at -20°C for 24 hours to form, and freeze-dried for about 12 hours to obtain a sponge-like three-dimensional porous collagen scaffold material. The material was mineralized in a twenty-four-well plate for 7 days, the temperature was maintained at 37°C, 1 mL of mineralization solution (Table 1) was added to each well of the three-dimensional porous collagen scaffold material, and the mineralization solution was replaced every 2-3 days. Thus, the ss-HMC / Zn of Example 2 was obtained.

[0094] Comparative Example 1

[0095] A commercially available pure Zn membrane (purity 99.998%, thickness 30 μm) was used as the guided bone regeneration membrane.

[0096] Comparative Example 2 (without mineralization treatment)

[0097] The pure Zn film (purity 99.998%, thickness 30μm) sample was immersed in a mixed solution of zinc nitrate (ZnNO3[aq], 0.07M) and phosphoric acid (H3PO4[aq], 0.15M), the pH was adjusted to 2.5, and the sample was immersed for 60s. The zinc film after acid etching was ultrasonically cleaned at 55℃ and 36kHz in the order of distilled water, acetone and anhydrous ethanol for 1-2 minutes. The treated sample was vacuum dried.

[0098] A type I procollagen solution (Corning, NY, USA, 3500 Da) with a procollagen molecule concentration of 1 mg / mL was dripped onto the Zn surface at a rate of 1 mL / min and self-assembled for 24 hours to form a collagen fibril layer. Thus, the guided bone regeneration membrane (ss-HC / Zn) of Comparative Example 2 was obtained.

[0099] Blank group: The blank group is a rat skull defect group without membrane and without bone powder.

[0100] Test Example 1: Characterization Test

[0101] The morphology of the zinc film surface, interface and collagen surface of ss-HC / Zn of Comparative Example 2, Example 1 and Example 2 were observed by SEM (Hitachi S-4800). Figure 2A, 2B, and 2C. The results show that the covalently surface-modified zinc surface of Example 1 presents a rough, high-surface-area quadrilateral cone structure. The micro-polished zinc surface of Example 2 presents irregular protrusions and cracks; from the cross-section, the covalently surface-modified cross-section forms a tight interlocking structure, and the micro-polished cross-section shows obvious cracks. Figure 2 C shows the hierarchical filamentous substructure of the collagen fibril clusters and the characteristic periodic ribbon-like pattern of mineralized fibrils (evidence that the collagen fibers are bonded together by calcium phosphate), similar to native bone.

[0102] The surface distribution of main elements of ss-HMC / Zn in Example 1 was detected by EDS spectrometer (Hitachi S-4800). The results are as follows: Figure 3 As shown in A. Figure 3 Energy dispersive X-ray spectroscopy (EDS) shown in A confirms the presence of Zn, P, and Ca ( Figure 3 A).

[0103] The characteristic functional group structures of ss-HMC / Zn of Example 1 and ss-HC / Zn of Comparative Examples 1 and 2 were determined by Fourier transform infrared spectrometer (FTIR, LUMOS II, Bruker, USA). The results are as follows: Figure 2 D. Fourier transform infrared spectroscopy (FTIR) characterized the typical collagen (1577-1727cm -1 ) and phosphate (900-1200cm -1 ) Functional group structure( Figure 2 D).

[0104] The yield strength and maximum tensile modulus of the samples of Comparative Example 1, Comparative Example 2 and Example 1 were measured using an electronic universal testing machine (Z0207; ZwickRoell, Germany). Figure 2 As shown in Figures 2E and 2F, in terms of mechanical strength, the yield tensile strengths of the films of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss HC / Zn) and Example 1 (ss HMC / Zn) are 52.48±5.00, 41.78±2.78 and 47.45±1.58 MPa, respectively; the maximum tensile strengths are 66.48±0.87, 45.63±1.17 and 58.1±4.47 MPa, respectively, which are much higher than that of the Bio-Gide film (3.7 MPa), indicating that ss-HMC / Zn has the ability to resist soft tissue collapse.

[0105] The hydrophilicity of the surfaces of the samples of Comparative Example 1, Comparative Example 2 and Example 1 was measured using a contact angle meter (OCA15EC and SCA20 software, DataPhysics, Filderstadt, Germany). Figure 2 As shown in G.

[0106] The presence of ss-calcium phosphate in the EDS spectrum of ss-HMC / Zn and the observation of transmission electron microscope TEM instrument (JEOL JEM-1011) proved the existence of apatite crystals ( Figure 3 ). Both EDS and TEM confirmed the presence of apatite crystals and abundant calcium and phosphorus elements in HMC ( Figure 3 ).

[0107] In terms of hydrophilicity, the contact angles of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss HC / Zn) and Example 1 (ss HMC / Zn) were 99.35±0.78°, 73.65±1.67° and 55.87±4.5°, respectively. After HMC and Zn were co-assembled, the contact angle of the surface was slightly smaller, indicating that the hydrophilicity increased (p<0.05) ( Figure 2 G).

[0108] Test Example 2: In vitro test of the effect of functionalized mineralized collagen coating on zinc film degradation and zinc ion sustained release

[0109] According to GB / T 16886, the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss HC / Zn) and Example 1 (ss HMC / Zn) were placed in vitro at 1.25 cm 2 / mL standard was immersed in physiological saline for 28 days to observe the effect of self-assembled functional mineralized collagen on zinc film degradation and sustained release of zinc ions. The results of zinc ion concentration determination showed that both HMC and HC effectively alleviated the sudden release of zinc ions ( Figure 4 ).

[0110] Test Example 3: In vitro test for biocompatibility

[0111] The biocompatibility of the samples of Comparative Example 1, Comparative Example 2 and Example 1 was tested in vitro by live-dead staining, CCK-8 test, immunofluorescence staining and electron microscopy observation. The test cells were human bone marrow stem cells (American Sciencell Company, item number: 7500, batches: 6899, 6881, 6890). The toxicity of the materials to the cells was tested by live-dead staining within 24 hours after inoculation, the adhesion performance and morphology of the materials to the cells, and the stretching performance of the cells on the materials at the microscopic level were tested by immunofluorescence and electron microscopy observation, and the cell activity within 5 days after the cells were inoculated on the materials was tested by CCK-8 experiment.

[0112] Figure 5A: Immunofluorescence photos of live-death detection of human bone marrow stem cells inoculated on samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) one day after inoculation; B: Immunofluorescence staining photos of human bone marrow stem cells inoculated on samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) one day after inoculation; C: SEM photos of human bone marrow stem cells inoculated on samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn); D: Cell activity of human bone marrow stem cells inoculated on samples of blank control, Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) within 5 days through CCK-8 experiment.

[0113] The results show that the ss-HMC / Zn film of Example 1 can promote cell adhesion and proliferation compared with the pure zinc film of Comparative Example 1, and has no obvious toxic effect on cells. The cells show better cell morphology on the surface coated with functional mineralized collagen (HMC) ( Figure 5 AD).

[0114] Test Example 4: In vitro and in vivo experimental detection of the regulatory effect on osteogenic differentiation of human bone marrow stem cells

[0115] The in vitro osteogenesis experiment was verified by qPCR, immunofluorescence, ALP staining and ARS staining. 4 The samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss HC / Zn) and Example 1 (ssHMC / Zn) were cultured for osteogenic induction for 7 and 14 days, and then relevant tests were performed.

[0116] Figure 5E: Immunofluorescence staining photos of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 7 days of osteogenic induction culture; F: ALP staining photos of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 7 days of osteogenic induction culture; G: The expression of RUNX2 and ALP of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 7 days of osteogenic induction culture; H: Immunofluorescence staining photos of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture Tablets; I: ARS staining photos of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture; J: Expression of BMP2 and OCN of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture; K: ALP values ​​of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 7 days of osteogenic induction culture; and L: Optical density values ​​(OD values) of the samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) after 14 days of osteogenic induction culture.

[0117] qPCR results showed that the expression of RUNX2, ALP, BMP2 and OCN in ss-HMC / Zn was higher than that in ss-HC / Zn and pure zinc film; immunofluorescence results showed that the expression of RUNX2 and OCN in ss-HMC / Zn was also significantly increased; ALP staining and ARS staining results both showed that ss-HMC / Zn promoted the osteogenic differentiation of human bone marrow stem cells ( Figure 5 F, 5I). In vivo experiments, samples of Comparative Example 1 (pure zinc film), Comparative Example 2 (ss-HC / Zn) and Example 1 (ss-HMC / Zn) were implanted into rat skull defects for 6 and 12 weeks, respectively. Micro-CT and immunohistochemistry results showed that the ss-HMC / Zn group of Example 1 had the best osteogenesis. Without adding exogenous growth factors or stem cells, it can guide and promote in situ bone regeneration ( Figure 5 AC).

[0118] Test Example 5: In vivo experimental detection of the intrinsic mechanism promoting skull defect in rats

[0119] The intrinsic mechanism of ss-HMC / Zn in promoting osteogenesis was explored and detected through transcriptome analysis and immunofluorescence. Figure 6A: The samples of blank control, comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) were implanted into rat skull defects, and after 6 weeks of observation, the in vivo osteogenesis was observed using Micro-CT, H&E, and Masson staining; B: The samples of blank control, comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) were implanted into rat skull defects, and after 12 weeks of observation, the in vivo osteogenesis was observed using Micro-CT, H&E, and Masson staining; C: The samples of blank control, comparative example 1 (pure zinc film), comparative example 2 (ss-HC / Zn) and example 1 (ss-HMC / Zn) were implanted into rat skull defects, and the bone density (BMD) and bone volume (BV) were detected by Micro-CT after 6 and 12 weeks of implantation.

[0120] The analysis results showed that ss-HMC / Zn could activate multiple pathways related to osteogenesis, angiogenesis, and cell recruitment; immunofluorescence results showed that ss-HMC / Zn could promote the high expression of VEGF, BMP2, and CD206 in the defect area in vivo, which further indicated that ss-HMC / Zn could promote the expression of angiogenesis, osteogenesis, and M2 macrophage polarization ( Figure 7 ).

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the above embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. Any changes or replacements that can be easily thought of by those skilled in the art within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.

Claims

1. A guided bone regeneration membrane, characterized in that include: a substrate layer comprising at least 99% by weight zinc; as well as At least one self-assembled mineralized collagen layer is disposed on the substrate layer and comprises collagen fibers and apatite crystals bonded to the collagen fibers.

2. The guided bone regeneration membrane according to claim 1, characterized in that: The mineralized collagen layer is formed by first forming a porous collagen scaffold layer on a substrate layer, and then catalyzing the mineralization liquid in the pores of the collagen scaffold layer with polyacrylic acid as a catalyst, wherein the composition of the mineralization liquid is: Wherein, relative to the total amount of the mineralization solution, the concentration of polyacrylic acid is 0.20-0.30 mM.

3. The guided bone regeneration membrane according to claim 1, characterized in that: The substrate layer is a zinc film that has been surface pretreated, wherein the surface pretreatment is selected from any one or both of acid etching pretreatment in a phosphoric acid solution with a pH value of 2-3 and mechanical grinding pretreatment using sandpaper with multiple different particle sizes.

4. The guided bone regeneration membrane according to any one of claims 1 to 3, characterized in that: The thickness of the mineralized collagen layer accounts for 74-80% of the total thickness of the guided bone regeneration membrane, wherein the content of the collagen fibers in the mineralized collagen layer is 80 wt %-85 wt %, and the content of the apatite crystals is 15 wt %-20 wt %, and The guided bone regeneration membrane has a yield strength of 45-80 MPa, an ultimate tensile strength of 55-80 MPa, and a water contact angle of 30-53°.

5. A method for preparing the guided bone regeneration membrane according to claim 1, characterized in that The following steps are involved: S1-providing a substrate layer, the substrate layer comprising at least 99% by weight of zinc; S2-applying a collagen solution on the substrate layer to allow the collagen to self-assemble into a collagen fiber layer, and drying and shaping to form a porous scaffold layer; as well as S3- Adding mineralizing liquid into the pores of the porous scaffold layer to perform mineralization treatment, and catalyzing the mineralizing liquid in the pores of the collagen scaffold layer to form apatite crystals, thereby obtaining the guided bone regeneration membrane.

6. The preparation method according to claim 5, characterized in that: The substrate layer is subjected to surface pretreatment before step S2, and then the collagen solution is applied to the pretreated substrate layer, wherein the surface pretreatment comprises at least one of the following: A) Pre-treatment of the substrate layer by acid etching in a mixed solution of zinc nitrate and phosphoric acid at a pH of 2-3, or B) The substrate layer is mechanically ground with silicon carbide sandpaper of 600, 800, 1200, 1500 and 2000 meshes in sequence.

7. The preparation method according to claim 5 or 6, characterized in that Step S2 includes dripping a type I procollagen solution having a concentration of 0.5-2.0 mg / ml onto the substrate layer at a rate of 0.5 to 2 ml / min, self-assembling for 24-48 hours, and then freeze-drying for 12-24 hours to dry and shape.

8. The preparation method according to claim 7, characterized in that The method further comprises: After the surface pretreatment, before step S3, the surface treated substrate is ultrasonically cleaned at 40-60° C. for 1-2 minutes using distilled water, acetone and anhydrous ethanol, respectively, and / or Step S3 includes adding 1-3 ml of the mineralization solution into each of the pores, replacing the mineralization solution every 2-3 days, and continuously mineralizing at 25-37° C. for 5-10 days.

9. Use of the guided bone regeneration membrane according to any one of claims 1 to 4 in the preparation of a medical material for promoting in situ bone regeneration in vivo.

10. The use according to claim 9, characterized in that The promoting in situ bone regeneration in vivo is selected from at least one of promoting in situ bone regeneration in vivo by promoting cell recruitment, promoting in situ bone regeneration in vivo by promoting M2 macrophage polarization, promoting in situ bone regeneration in vivo by enhancing vascularization, and promoting in situ bone regeneration in vivo by activating BMP2-related pathways.

Citation Information

Patent Citations

  • Bone tissue repair biological material and preparation method thereof

    CN104495862A

  • Method for preparing mineral collagen coating on surface of medical implantation body

    CN104790007A

  • Self-mineralized collagen membrane, preparation method and application

    CN112206359A

  • Mineralized collagen material as well as preparation method and application thereof

    CN117138113A

  • Biomimetic bone composite material, a preparation method and uses thereof

    US20210038760A1